The transversal strength comparison between polyethylene and glass fiber as an acrylic resin denture plate repair material - Pramudya Aditama; Erwan Sugiatno; Sabdayana Sabdayana (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Acrylic resin is the most commonly used denture base material. However, it has a shortage of being easily broken. One way to resolve this problem is by adding polyethylene (PE) or glass fibers. The purpose of this research is to compare the transversal strength of PE and glass fibers from denture plate acrylic resin repair material. The experiment involved 32 plates of heat cure acrylic with the dimensions of 65 mm x 10 mm x 2.5 mm. The speciments were prepared to create a 3 mm gap and 45° bevel. Subjects were divided into 2 groups, each group containing 16 plates. Group I was reinforced with PE fiber and Group II was reinforced with glass fiber. All plates were soaked in distillation water for one day at 37 °C. Plates were tested for transverse strength with universal testing machine and all data were analyzed with independent t-tes at 95% confidence level. Macro photo analysis was used to observed the bond failure on fiber and resin. The mean of transverse strength (MPa) denture plate acrylic resin repair material reinforced with PE fiber was (67.38 ± 4.31) MPa, while glass fiber was (93.61 ± 6.14) MPa. Independent t-tes showed that type of fiber had a significant effect (p<0.05). Thus, it is possible to conclude that addition of glass fibers in denture plate acrylic resin repair material increased the transverse strength and made it stronger than those added with PE fibers.